Pengaruh Senam Hamil Terhadap Kelancaran Proses Persalinan Kala II di Bidan Praktek Swasta Anik Hanifa Winong Gempol Pasuruan - Ety Diana Sulistyawati; Aprilya Tunggo Dewi (NHM PRESS, 2022)
In the delivery process, there are several factors which can influence the smoothness of childbirth process, which one of theme is influenced by abdomen pushing power which can be anticipated by performing pregnancy gymnastics which can influence childbirth process smoothness, fore there researcher wish to discover the influence of pregnancy gymnastics on childbirth process in Anik Hanifa Public Midwifery Practice Winong Gempol District of Pasuruan City.The general aim of this research to discover the influence of pregnancy gymnastics on childbirth process smoothness, while its specific aim is to identify the characteristics of mothers giving birth who perform pregnancy gymnastics in there pregnancy periods, to identify childbirth process and to analyze the influence of pregnancy gymnastics on childbirth process smoothness.Type of this research is analytical which control approach using research instrument of questionnaire and observation sheet completed which checklist. Sample used are same mothers giving birth who perform pregnancy gymnastics and those who do not perform pregnancy gymnastics in the Sukemi Public Midwifery Practice beginning from April- May 2007, totalling 30 respondents.Data obtained is processed using chi- square test (X²) with significant level of α = 0,05 research result indicate that there is a reasonable relation between pregnancy gymnastics and childbirth process smoothness with value of P= 0,007Most respondent performing pregnancy gymnastics a experiencing childbirth process faster than those who do not perform pregnancy gymnastics, suggestion proceeded is that midwife is expected to provide guidance to pregnant mothers about the importance of performing pregnancy period to smoothness childbirth process.